Blue-Light-Regulated Expression of Genes for Two Early Steps of Chlorophyll Biosynthesis in Chlamydomonas reinhardtii. - Matters, G. L. (1995)
In light:dark-synchronized cultures of Chlamydomonas reinhardtii, the genes encoding the enzymes for two early steps of chlorophyll biosynthesis, glutamate-1-semialdehyde aminotransferase (gsa) and [delta]-aminolevulinic acid dehydratase (alad), are expressed at high levels early in the light phase, just prior to a rapid burst of chlorophyll synthesis. Induction of gsa mRNA in synchronized cells is totally dependent on light, whereas induction of alad mRNA occurs to approximately one-half the light-induced level even in cells kept in the dark during the light phase and appears to be dependent on the cell cycle or a circadian rhythm. gsa mRNA and alad mRNA accumulation is induced by light that was passed through blue (400-480 nm) or green (490-590 nm) filters but not by light that was passed through orange (>560 nm) or red (>610 nm) filters, indicating the participation of a blue-light photoreceptor system rather than a protochlorophyllide- or rhodopsin-based photoreceptor. Light induction of gsa mRNA accumulation is absent in a carotenoid-deficient mutant, which suggests that a carotenoid-containing blue-light photoreceptor is involved. In contrast, pretreatment of wild-type cells with either of two flavin antagonists, phenylacetic acid and KI, does not prevent the light induction. In the later part of the light phase, the gsa mRNA level decreases more rapidly than that of alad mRNA. Turnover studies indicate that the half-life of alad mRNA is twice that of gsa mRNA. This difference in mRNA stability partially accounts for the more rapid decline in gsa mRNA levels after the peak of light induction is reached. Thus, differential blue-light induction and stability of mRNAs regulates the expression of these two chlorophyll biosynthetic genes.